Role of Tengganai in Resolving Domestic Conflicts: A Maqashid Shariah Analysis - Asnadi Anas; Ahmad Zuhdi (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study investigates the role of tengganai in resolving domestic conflicts and analyzes the practice within the framework of maqashid shariah. Using a qualitative case study approach, data were collected through interviews and observations with tengganai, customary leaders, and related stakeholders. The findings indicate that tengganai act as mediators who emphasize deliberation and familial approaches through the mechanism of sit tengganai. This mechanism has proven effective in resolving disputes swiftly, efficiently, and with respect for the dignity of the parties involved. Nevertheless, a shift has occurred in which the enforcement of customary sanctions has become less consistent, with greater reliance on persuasive methods. From the perspective of maqashid shariah, this practice reflects efforts to safeguard religion, life, intellect, lineage, and property, thereby illustrating the contextual application of living maqashid. The study highlights the importance of tengganai as local actors in integrating customary law and Islamic law in domestic conflict resolution.